Emotional experience and prosocial behavior in observers of unjust situations - Doorn, Janne van (Applied psychology in criminal justice, 2019)
Five studies tested the emotional experience and prosocial motivations in observers (i.e., third parties) of unjust situations. Studies 1 and 2 found that anger was the most dominant emotion experienced in unjust situations, and that prosocial behavior towards a victim decreased when justice had already been restored by compensation of the victim. Study 3 added that the experience of anger also decreases when justice is restored. Study 4 generalized the effects to different types of compensation. Study 5 switches to the perspective of the victim, showing a larger decrease in the most dominant emotion anger when justice was restored by means of compensation than by punishment. The implications of these findings with regard to third-party emotions and behavior in unjust situations are discussed.